Relevansi Aliran Pendidikan Dengan Sistem Pembelajaran Di Madrasah Ibtidaiyah - Ahmad Suhadi; Ade Nofita Karim; Gesti Anggraeni Pamungkas; Novita Ramadani; Nurul Efi; Siti Fatimah; Atim Rinawati (IAINU Kebumen, 2023)
Education is a process of learning about knowledge, skills, and habits that can be done anywhere and anytime. In education, there are various thoughts about education or also known as schools of education. The purpose of this study was to find out the relevance between educational streams and learning at Madrasah Ibtidaiyah Kebumen. This type of research used qualitative methods. The subject of this study used three Islamic elementary schools in Kebumen. Data collection techniques using observation data, interviews, and documentation. The analysis technique used is data reduction, data presentation, and conclusions. There are several types of educational streams that are used as a reference for educators, including (1) classical school consisting of Convergence and Naturalism; (2) the modern stream consists of Progressivism and Existentialism. This flow was implemented because it was relevant to the learning system implemented in several schools at Madrasah Ibtidaiyah Kebumen.